Preserving Artistic Legacies: Legal Safeguards for Intellectual Property Rights in the Music Industry - Dijan Widijowati (LifeSciFi, 2023)
The preservation and protection of artistic legacies in the music industry have become increasingly crucial in an era marked by digital proliferation and widespread accessibility. This paper explores the topic of legal safeguards for intellectual property rights (IPR) in the music industry, focusing on the significance of copyright protection, licensing agreements, and the enforcement of legal provisions. The challenges posed by digital piracy, unauthorized distribution, and emerging technologies are examined, considering their transformative impact on music consumption and copyright enforcement. The paper emphasizes the importance of comprehensive policies and effective legal frameworks to address these challenges and ensure the integrity of intellectual property rights. It highlights the role of public awareness, education campaigns, and international cooperation in cultivating respect for intellectual property rights and discouraging piracy. By recognizing the value of intellectual property rights, nations can create an environment that fosters creativity, innovation, and sustainable progress in the music industry. The findings of this paper provide valuable insights for policymakers, industry professionals, and artists, contributing to a deeper understanding of the critical role played by legal mechanisms in preserving and sustaining artistic legacies.